Diabetes: influence of carbohydrates in the associated pathologies - Carvalho, M. M. S.; Correia, M. G. S.; Santos, H. J. X. (Scientia Plena, 2012)
This article discuss about which the amount of carbohydrate ingested by the diabetic patient influences the pathologies that may be associated, since this is the nutrient that most affects the rate of blood sugar after a meal. By the fact that diabetes causes dysfunction and failure of various organs, this research aims the paper aims to identify the complications arising from it and analyze the influence of inappropriate ingestion of carbohydrate on blood glucose levels. In order to do such thing dietary survey was applied, "24-hour recalls," the older diabetic group PAIMI – Program of Integral Assistance to the Best Age, from Tiradentes University, however the outcomes were not consistent for a conclusion about the influence of carbohydrates associated with diabetes possibly due to the size of the sample. However, it remains evident that the lack of control of DM results in damage to the body and a high probability of developing complications. Although there is no permanent cure, a diet low in refined carbohydrates and high in soluble fiber, along with changes in the lifestyle, including the performance of physical activity are essential for both the treatment of diabetes, and prevention for those who possess risk factors but don’t have the disease yet.